Kajian Terhadap Perawi Layyin Dalam Hadith Mengenai Tayamum Selepas Wuduk - Wan Kamal NadzifWan Jamil; Roshimah Shamsudin; Norazmi Anas; Nurul Khairiah Khalid; Shahril Nizam Zulkipli (USIM Press, 2024)
Vol 5. No. 2 (December 2020)